Self-reported Oral and Dental Health Status among the Pregnant Women of a Selected Hospital in Dhaka City (Bangladesh Journal of Dental Research & Education, 2014)
Aims: The aims of this study were to gain an understanding of pregnant women s oral hygiene practices and to assess the oral and dental health status. Materials and Methods: A semi - structured questionnaire was completed by 100 pregnant women of the gynecology department of Dr. Akhter Jahan Mirza Hospital, Dhaka. Results: The women in this study 40% were in 19-22 years age group. Forty eight percent (48%) women of the subjects were having up to high school level education & 28% had low income of Sixty Thousand to One Lac taka yearly. In relation to oral hygiene habit before pregnancy majority of the women (56%) stated that they brush their teeth once a day, 19% use dental floss and 14% use mouth rinse once a day. During pregnancy women seemed to be slightly more concerned about oral hygiene but not significantly. Only 66% brush their teeth and 17% floss their teeth and 18% use mouth rinse once a day during pregnancy. The major problem in their mouth noticed by the women during pregnancy was bleeding gums (58%). Conclusion: This study feels the necessity of giving special attention to pregnant women s oral health in Bangladesh. Women should be educated on good oral hygiene practices so as to minimize prevalence of poor maternal oral health during pregnancy. DOI: http://dx.doi.org/10.3329/bjdre.v4i2.20251 Bangladesh Journal of Dental Research and Education Vol.4(2) 2014: 61-64